Resveratrol Attenuates High Glucose-Induced Vascular Endothelial Cell Injury by Activating the E2F3 Pathway. (28th April 2020) - Ding, Xiaolian; Yao, Wei; Zhu, Jie; Mu, Kaida; Zhang, Jing; Zhang, Jin-an
Abstract : Type 2 diabetes mellitus (T2DM) is the most common metabolic disease. High glucose-induced macrovascular disease and microangiopathy are major complications of diabetes. E2F3, a member of the E2F transcription factor family, is closely related to cardiovascular diseases. Resveratrol, a nonflavonoid polyphenolic compound widely found in plants, has been shown to have cardiovascular protection. However, there are few studies on whether resveratrol can effectively treat diabetic angiopathy, and the specific mechanism involved needs further study. This study investigated whether E2F3 transcription factors are involved in the process of vascular endothelial injury induced by high glucose and observed its effects on the proliferation of vascular endothelial cells. Then, it analyzed whether resveratrol can inhibit high glucose-induced vascular endothelial cell injury by regulating the E2F3 pathway. We demonstrated that the expression level of the E2F3 transcription factor was significantly inhibited in high glucose state. Resveratrol inhibited high glucose-induced vascular endothelial cell injury by upregulating the E2F3 pathway. High glucose can induce vascular endothelial injury by inhibiting E2F3 gene expression, while resveratrol can inhibit high glucose-induced vascular endothelial injury by activating the E2F3 pathway.